2022
DOI: 10.1071/fp21363
|View full text |Cite
|
Sign up to set email alerts
|

Short-term elevated temperature and CO

Abstract: The continuous increases of atmospheric temperature and CO 2 concentration will impact global photosynthesis. However, there are few studies considering the interaction of elevated temperature (eT) and elevated CO 2 (eCO 2 ) on dynamic photosynthesis, particularly for C 4 species. We examine dynamic photosynthesis under four different temperature and [CO 2 ] treatments:(1) 400 ppm × 28°C (CT); (2) 400 ppm × 33°C (CT+); (3) 800 ppm × 28°C (C+T); and (4) 800 ppm × 33°C (C+T+). In Glycine max L., the time require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Recent research in three phylogenetically linked pairs of C3 and C4 species from the Alloteropsis , Flaveria and Cleome genera indicated that photosynthetic induction was slower in C4 than in C3 species [ 65 ]. Zheng also reported that photosynthetic induction was much faster in the C4 species Amaranthus tricolor than in the C3 species Glycine max ; in addition, this research reported that short-term elevated temperature and carbon dioxide conditions promoted photosynthetic induction in the C3 species Glycine max , but not in the C4 species Amaranthus tricolor [ 66 ].…”
Section: Effects Of Non-environmental Factors On Dynamic Photosynthes...mentioning
confidence: 99%
“…Recent research in three phylogenetically linked pairs of C3 and C4 species from the Alloteropsis , Flaveria and Cleome genera indicated that photosynthetic induction was slower in C4 than in C3 species [ 65 ]. Zheng also reported that photosynthetic induction was much faster in the C4 species Amaranthus tricolor than in the C3 species Glycine max ; in addition, this research reported that short-term elevated temperature and carbon dioxide conditions promoted photosynthetic induction in the C3 species Glycine max , but not in the C4 species Amaranthus tricolor [ 66 ].…”
Section: Effects Of Non-environmental Factors On Dynamic Photosynthes...mentioning
confidence: 99%
“…Net CO 2 assimilation in amaranth decreased an average of 33% compared with the control. Zheng et al (2022) conducted similar work with Glycine max or soybean (C 3 ) and Amaranthus tricolor (C 4 ) in China. There were four combinations of temperature (28° or 35°C) and CO 2 (400 or 800 ppm) with a PPF of 600 µmol per m 2 per s. In Glycine max, high temperatures increased gas exchange under both low and high CO 2 compared with the other regimes.…”
Section: Effect Of Climate Change On Photosynthesis Leaf Area Expansi...mentioning
confidence: 99%
“…However, crops with a C 4 photosynthetic pathway (e.g., maize and sugarcane) profit from this condition. It appears that C 4 plants benefit from climate change and increased temperatures due to the nature of their photosynthetic system; however, temperatures above 38°C inhibit photosynthesis (Zheng et al, 2022), whereas warming at night raises respiration costs without any potential benefit for photosynthesis (Sadras, Calderini, 2015). Thirdly, warming raises the vapor pressure deficit (VPD) between air and the leaf and increases transpiration and water loss.…”
Section: Plant Tolerance To High Tem-perature In a Changing Envi-ronmentmentioning
confidence: 99%